PEMIKIRAN TENTANG PENDIDIKAN PESANTREN - Abdurrahman Abdurrahman (LP3M IAI Al-Qolam Malang, 2018)
Pesantren as educational institutions that have strong influence (indigenous) in Indonesian Muslim community. Pesantren when compared to educational institutions that have appeared in Indonesia, are the oldest educational system and are considered as Indonesian cultural products. Pesantren as Islamic educational institutions that began in the wake of the Islamic community in Nusantara. We know at least four elements of Pesantren; mosque or mushalla, yellow book (kitab kuning) learning, santri, and kiai. Kiai in pesantren are often referred to as founders or educator of pesantren. There are at least three types of Pesantren in Indonesia; Traditional Pesantren (salaf), Modern Pesantren (khalaf/'Ashr?), Comprehensive Pesantren (sy?mil?). Besides introducing Pesantren as an educational institution, the author also expressed various thoughts about the education system; regarding the functions, developing the potential, revitalizating of modeling systems, cultural maintenance, and high scientific culture. The author concludes that the traditionality of Pesantren should be aimed at a noble tradition in various ways, including the pesantren intellectual tradition that has not stopped until now. Keywords: Pesantren, Education System